Evaluasi Kemampuan Lahan Dan Arahan Pemanfaatan Lahan Di Daerah Aliran Sungai Wai Tina Kabupaten Buru Selatan Provinsi Maluku - Jeheskel Manuputty; Elia Y Gaspersz; Selwanus M Talakua (Faculty of Agriculture, Pattimura University, 2014)
Tina Wai watershed area 48,132 ha, located in the South Buru and serves as a provider of water for the local community. Land Capability Evaluation and Tina Wai Watershed Land Use in South Buru, Maluku Province, has been performed in order to determine the land capability classification level, and determine the direction and pattern of land use in accordance with their respective land capability class. The research method is a survey method with a pattern of synthetic and analytical approach with a flexible range of observation following the change in shape of physiographic and land use. The results found that Tina has 6 Wai watershed land capability class, ie class III, IV, V, VI, VII, and VIII with factor inhibiting dominated by undulating slopes to very steep, erosion rates to very heavy weight, medium texture soil, permeability rather fast to slow, moderate sensitivity to erosion, rock gravel of moderate-to-many, and the threat of flooding rather frequently. Land capability class has the most extensive is the fourth grade with an area of 24.636 ha, or 51.19%. Referrals for agricultural land use is 29,184.75 ha or 61.89; for plantations, livestock and forest production by 8396.75 ha or 17.38%; for the protected forest of 6,941.25 ha or 14.42%; and for the nature reserves of 3036.00 ha or 6.31%.